The Village Industrialization and Civilization: A Critical Reading - Shahrin, Attori Alfi; Fawaid, Yazidul; Masruroh, Nikmatul; Umamah, Lidhatul; Dono Hariyanto, Al Furqon (Universitas Darussalam Gontor, 2023)
This study case aims, 1) to explore the trend of industrialization in Indonesia, especially in villages areas, 2) to criticize industrialization in villages areas using environmental sustainability studies, 3) to analysis and studies till related to village industrialization from the perspective of maqashid sharia. This analysis goal was achieved by using a qualitative approach with the type of digital and industrial village case studies in the East Java region. Data were collected by observation, interviews, documentation and FGD then analyzed using critical analysis. Data validity uses source triangulation. The research results, 1) the trend of industrialization in villages areas has a positive impact on economic growth, but has changed the rural structure from agrarian to industrial and digital villages. 2) Industrialization in villages areas is contrary to the concept of environmental sustainability, 3) Village industrialization from maqashid shariah studies provides benefits from the perspective of hifdz an nafs, hifdz al 'aql, hifdz al mal and hifdz al bi’ah. However, from the point of view of hifdz ad din and hifdz al nasl, it cannot be categorized as mashlahah, because the presence of village industrialization besides having an impact on environmental damage can also result in moral degradation.